Réponses

2014-01-30T22:27:42+01:00
C = (3x + 3)(4x - 6)
C = (12x² - 18x + 12x -18
C = 12x² -6x -18
Pour x = 0  => on a C = -18
Pour x = 1  => on a C = -12

D = (x - 7)(5x + 11)
D = 5x² + 11x - 35x - 77
D = 5x² -24x - 77
Pour x = 7 => on a D = 0

E = (5 - 9x)(3x - 8)
E = 15x - 40 -27x² +72
E = -27x² + 87x - 40
Pour x = -1 => on a E = 100

F = 4(7 -5a)+5(2a -3)
F = 28 - 20a + 10a -15
F= -10a +13
Pour x =  \frac{3}{10} => On a F = 10

G= 3(5a -2)(1 + 4a)
G = 3 (5a+20a² -2 -8a)
G = 15a +60a² -6 -24a
G= 60a² -9a -6
Pour x = 0 => on a G = -6
Pour x = 1=> on a G = 45

Vérifie bien mes calculs une erreur de signe peut complètement changer le résultat !